Transcriptome analysis of the painted lady butterfly, Vanessa cardui during wing color pattern development. (December 2016) - Connahs, Heidi; Rhen, Turk; Simmons, Rebecca
Abstract Background Butterfly wing color patterns are an important model system for understanding the evolution and development of morphological diversity and animal pigmentation. Wing color patterns develop from a complex network composed of highly conserved patterning genes and pigmentation pathways. Patterning genes are involved in regulating pigment synthesis however the temporal expression dynamics of these interacting networks is poorly understood. Here, we employ next generation sequencing to examine expression patterns of the gene network underlying wing development in the nymphalid butterfly, Vanessa cardui . Results We identified 9, 376 differentially expressed transcripts during wing color pattern development, including genes involved in patterning, pigmentation and gene regulation. Differential expression of these genes was highest at the pre-ommochrome stage compared to early pupal and late melanin stages. Overall, an increasing number of genes were down-regulated during the progression of wing development. We observed dynamic expression patterns of a large number of pigment genes from the ommochrome, melanin and also pteridine pathways, including contrasting patterns of expression for paralogs of the yellow gene family. Surprisingly, many patterning genes previously associated with butterfly pattern elements were not significantly up-regulated at any time during pupation, although many other transcription factors were differentially expressed. Several genes involved in Notch signaling were significantly up-regulated during the pre-ommochrome stage includingslow border cells, bunched andpebbles ; the function of these genes in the development of butterfly wings is currently unknown. Many genes involved in ecdysone signaling were also significantly up-regulated during early pupal and late melanin stages and exhibited opposing patterns of expression relative to the ecdysone receptor. Finally, a comparison across four butterfly transcriptomes revealed 28 transcripts common to all four species that have no known homologs in other metazoans. Conclusions This study provides a comprehensive list of differentially expressed transcripts during wing development, revealing potential candidate genes that may be involved in regulating butterfly wing patterns. Some differentially expressed genes have no known homologs possibly representing genes unique to butterflies. Results from this study also indicate that development of nymphalid wing patterns may arise not only from melanin and ommochrome pigments but also the pteridine pigment pathway.